Mock interview : self-perceived competence and actual performance among ESL undergraduates - Asniza Mohamad Utama (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this paper is to investigate self-perceived competence and actual performance during mock interview among ESL undergraduates in Malaysia. This study investigates the differences between students’ self-perceived competence and actual performance in mock interviews. The study was conducted in Kulliyyah of Islamic Revealed Knowledge and Human Sciences at International Islamic University Malaysia (IIUM). The survey was distributed to 40 ESL undergraduates who were attending Language for Occupational Purposes (LE 4500) course. A descriptive quantitative method is used to examine the two variables involved in this study. The result revealed that students perform better than they think they are. The results of this study show that they underestimate their capability to do well in mock interview. This study helps to give instructors a better understanding about the student perspective. It could be implied students’ lack of confidence drives them to work harder in order to do well in the mock interviews.